Warping character animations using visual motion features. (February 2023) - Jovane, Alberto; Raimbaud, Pierre; Zibrek, Katja; Pacchierotti, Claudio; Christie, Marc; Hoyet, Ludovic; Olivier, Anne-Hélène; Pettré, Julien
Abstract: Despite the wide availability of large motion databases, and recent advances in exploiting them to create tailored contents, artists still spend tremendous efforts in editing and adapting existing character animations to new contexts. This motion editing problem is a well-addressed research topic. Yet only a few approaches have considered the influence of the camera angle, and the resulting visual features it yields, as a mean to control and warp a character animation. This paper proposes the design of viewpoint-dependent motion warping units that perform subtle updates on animations through the specification of visual motion features such as visibility, or spatial extent. We express the problem as a specific case of visual servoing, where the warping of a given character motion is regulated by a number of visual features to enforce. Results demonstrate the relevance of the approach for different motion editing tasks and its potential to empower virtual characters with attention-aware communication abilities. Graphical abstract: Highlights: A procedural animation technique to adapt the motion of virtual characters. Performing the analysis of low-level perception features from an observer point of view. Increasing the realism of interaction and the expressive capability of digital avatars. Increasing social presence in virtual reality applications. Inspired by robotics' visual servoing, and applied to virtual characters animation.